Revisión: evaluación del bienestar en gallinas ponedoras en sistemas al aire libre y bajo techo en jaula (2022)
The production of eggs for food has increased in recent decades with a volume of 68 million tons in the world, due to its protein and easy accessibility due to its low cost; this demand for the product has made that new methods are generated in the management of flocks, increasing production in function of supplying the demand which has generated a new problem the well-being of the hens (Albin et al., 2008).